Cross-border online shopping intention of Chinese consumers based on different cultural orientations. (29th March 2019) - Wu, Xiaosong; Liu, Shan; Wang, Na; Gong, Yeming
Foreign brand attitude and reference group influence are limited in terms of providing sufficient explanation to the cross-border online shopping (COS) behaviour of consumers. Therefore, two different cultural concepts and intercultural adaption should be considered in the COS context. This study chose healthy consumer ethnocentrism (CET) as a national-oriented cultural concept and intercultural sensitivity (ICS) as product country-of-origin-oriented cultural concept. Data analysis of 201 online questionnaires shows that foreign brand attitude and COS intention is positively affected by ICS but negatively influenced by healthy CET. Moreover, the influence of value-expressive reference group positively affects the COS intention. Given the moderating effect of gender, the influences of males and females on the COS intention have several differences. This study revealed the complex mentality of Chinese consumers during COS that is affected by cultural concepts of varying orientations.